Синергетичні моделі нелінійної динаміки - Хамаза, А. О. (ХНУРЕ, 2024)
Synergetics, as a field of study, has gained significant attention due to its ability to describe self-organization and cooperation in complex systems. Nonlinear dynamics, deterministic chaos, and fractal structures are fundamental concepts in synergetics, offering insights into the behavior of intricate systems. This paper aims to analyze synergetic models used to depict nonlinear dynamics, deterministic chaos, and fractal structures. Using mathematical and computational methods, we seek to explore the properties of these models and their applications across diverse scientific domains.
Keywords: синергетична модель; нелінійна динаміка